Eccrine Angiomatous Hamartoma - Gupta Monisha; Minocha Y.C (Wolters Kluwer Medknow Publications, 2002)
A case of eccrine angiomatous hamartoma on the wrist in a 15 year old girl is presented for its rarity. Histopathology revealed increased number of normal eccrine structures and numerous capillary channels in the dermis.